KORELASI RASIO KEUANGAN TERHADAP HARGA SAHAM DI PERUSAHAAN SEKTOR PROPERTI - Rifki Khoirudin; Uswatun Khasanah (LP2MTBM MAKARIOZ, 2022)
The property sector which experienced an increase can be seen from the number of construction, housing, apartments, hotels, houses, shops (shop houses), shopping centers, and office centers. This large amount of development indicates that there is a considerable market opportunity for the property sector in Indonesia. This information also has implications for investors' positive reactions to stock prices in property sector companies on the Indonesia Stock Exchange (IDX). The average stock (stock) has increased due to positive sentiment from investors to the company's performance expectations of the property sector issuers to obtain company profits. The higher profit obtained by the company will result in an increase in the company's stock price so that the higher the stock return is obtained (Jafar, 2012). The formulation in this study is how the influence of financial ratios on stock prices of property sector companies. From the results of the study, the results of Current Ratio (CR) Variables, Total Asset Turnover (TATO) Variables, Debt To Asset Ratio (DAR) variables have a significant positive effect on stock prices. While the Variables of Return On Assets (ROA) and Variables Earning per Share (EPS) do not have a significant positive effect on stock prices.